Peran Quality Assurance dalam Menjamin Produk Farmasi Sesuai Cara Pembuatan Obat yang Baik - Herman Widjaja; Lendi Mutia Suciana; Andika Saputra Wabula (Al-DYAS, 2026)
Although pharmaceutical quality standards have been regulated through Good Manufacturing Practice (CPOB), deviations in the production process still have the potential to affect the safety, efficacy, and public trust in pharmaceutical products. This study aims to examine the role of Quality Assurance in ensuring the conformity of pharmaceutical products with CPOB standards. This study used a narrative literature review method through the examination of scientific articles, regulations, and official guidelines related to pharmaceutical quality systems, process validation, internal audits, deviation management, Corrective and Preventive Action (CAPA), change control, Product Quality Review, data integrity, and quality risk management. Literature sources were obtained from Google Scholar, Garuda, SINTA, PubMed, ScienceDirect, Badan Pengawas Obat dan Makanan, the World Health Organization, the Pharmaceutical Inspection Co-operation Scheme, and the International Council for Harmonisation. The data were analyzed descriptively through source selection, thematic grouping, content interpretation, and comparison of national and international references. The review results show that Quality Assurance plays a role as a quality risk prevention system through document control, process validation, production supervision, internal audits, deviation investigations, CAPA, change control, batch release, and periodic quality evaluation. The conclusion of this review affirms that Quality Assurance functions not only as a final inspection mechanism but also as a guide for the quality system from the planning stage to continuous improvement. The implications of this review emphasize the importance of strengthening personnel competence, digitalizing documentation, quality culture, and evidence-based risk monitoring in ensuring the quality of pharmaceutical products.